Assessment of pleural fluid adenosine deaminase and alkaline phosphatase in tubercular and non-tubercular effusions - Santanu Mondal,; Swati Bhattacharyya,; Subhra Mitra, (Asian Journal of Medical Sciences, 2023)
Background: Many studies have showed that adenosine deaminase (ADA) and alkaline phosphatase (ALP) values were highly supportive in the diagnosis of tuberculosis but comparison between ADA and ALP has not been much documented in pleural fluid (PF) in eastern India. Hence, the main aim of the study was to identify the relation between ADA and ALP in diagnosis of tuberculosis if any. Aims and Objectives: This study was conducted to estimate and compare the levels of ADA and ALP of PF in tubercular and non-tubercular diseases. Materials and Methods: This study was hospital-based, cross-sectional, and observational study during the period of 1 year. A total of 90 patients have been analyzed among them after excluding few outliers, 82 patients had been taken whose ADA and ALP were measured in PFs. Results: Kolmogorov–Smirnov and Shapiro–Wilk tests for statistical analysis were used to determine whether continuous variables were normally distributed or not. In the comparison of tubercular and non-tubercular effusion groups, P-value for ADA in independent t-test was 0.000, and P-value for ADA and ALP in Mann–Whitney U-test was 0.000 and 0.000, respectively. Receiver operating characteristic (ROC) curve showed area under the curve (AUC) of 0.965 and 0.751 in ADA and ALP for diagnosing tuberculosis. Cutoff values of 31.87 IU/L for ADA were determined by ROC curve analysis with 100% of sensitivity and 82.3% of specificity and cutoff values of 40.5 IU/L for ALP were also determined by ROC curve analysis with 75.6% of sensitivity and 68.3% of specificity for diagnosis of tuberculosis. Conclusion: Although ADA is the best parameter for diagnosing tubercular pleural effusions, analysis of ALP is cost-effective.